Aboriginal children and penicillin injections for rheumatic fever: how much of a problem is injection pain?. (22nd November 2017) - Mitchell, Alice G.; Belton, Suzanne; Johnston, Vanessa; Read, Clancy; Scrine, Clair; Ralph, Anna P.
Abstract: Objective: To explore young Aboriginal people's and clinicians' experiences of injection pain for the 10 years of penicillin injections children are prescribed to prevent rheumatic fever recurrences. Methods: Aboriginal children on the penicillin regimen and clinicians were purposively recruited from four remote sites in Australia. Semi‐structured interviews and participant observations were conducted. Views were synthesised and thematically analysed. Results: A total of 29 Aboriginal children and 59 clinicians were interviewed. Sixteen participants appeared to become accustomed to the injection pain, eight did not find pain an issue, and five found injection pain difficult. A further five believed the injections made them unwell. Patients expressed varying abilities to negotiate with clinicians about the use of pain reduction measures. Clinicians revealed good knowledge of pain reduction measures, but offered them inconsistently. All clinicians found administering the injections distressing. Conclusion: Repeated painful procedures in children necessitate well‐planned and child‐focused care. Current practices are not in line with guidance from the Royal Australasian College of Physicians about effects of repeated painful procedures on children. Initiating the long‐term injection regimen for rheumatic fever is a special event requiring expert input. A newly reported finding of a subset of young people feeling unwell after receiving the injection requires further investigation. Implications for public health: Improvement of local and jurisdictional guidelines on use of pain reduction measures for children who have been prescribed repeated painful injections for rheumatic fever is needed.